Mathematical Programming Models for Capital Budgeting–A Survey, Generalization, and Critique - Bernhard, Richard H. (Journal of Financial and Quantitative Analysis, 1969)
Until very recently, in most work on normative models for capital investment planning, it has been assumed that availability of capital is unconstrained; i.e., that money may be freely borrowed or lent at a single market rate of interest, and that no other constraints affect the proper choice of available productive investment projects to be undertaken. Since practical situations almost universally do involve such constraints, the traditional theories have, for the most part, been an unsatisfactory guide to achievement of optimal capital investment behavior in the real world.